2020
DOI: 10.1177/1545968319893289
|View full text |Cite
|
Sign up to set email alerts
|

Position-Cortical Coherence as a Marker of Afferent Pathway Integrity Early Poststroke: A Prospective Cohort Study

Abstract: Background. Addressing the role of somatosensory impairment, that is, afferent pathway integrity, in poststroke motor recovery may require neurophysiological assessment. Objective. We investigated the longitudinal construct validity of position-cortical coherence (PCC), that is, the agreement between mechanically evoked wrist perturbations and electroencephalography (EEG), as a measure of afferent pathway integrity. Methods. PCC was measured serially in 48 patients after a first-ever ischemic stroke in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In line with our findings, in this study, it was concluded that PCC reflects afferent pathway integrity (Zandvliet et al, 2020b). However, where the present study did not show any effect of time on the evoked cortical response, Zandvliet and colleagues observed significant improvements in PCC in the first twelve weeks after stroke, which correlated with improvements in sensory and motor function within patients (Zandvliet et al, 2020b). Another study, that was performed in partially the same sample of patients as in the present study, investigated longitudinal changes in neural oscillations during resting state at electrode level as a function of time post stroke (Saes et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, in this study, it was concluded that PCC reflects afferent pathway integrity (Zandvliet et al, 2020b). However, where the present study did not show any effect of time on the evoked cortical response, Zandvliet and colleagues observed significant improvements in PCC in the first twelve weeks after stroke, which correlated with improvements in sensory and motor function within patients (Zandvliet et al, 2020b). Another study, that was performed in partially the same sample of patients as in the present study, investigated longitudinal changes in neural oscillations during resting state at electrode level as a function of time post stroke (Saes et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Next to integrity of the descending pathways, integrity of ascending somatosensory pathways seems to be an important predictor for motor function after stroke. In particular the proprioceptive system seems to play a crucial role in regaining control over motor tasks ( Vidoni and Boyd, 2009 ; Simo et al, 2014 ; Zandvliet et al, 2020a , b ). To assess the integrity of ascending pathways, previous studies used the upper extremity section of the Erasmus modified Nottingham Sensory Assessment (EmNSA-UE) ( Winters et al, 2016 ; Zandvliet et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…In future studies, it would be interesting to examine how targeted changes in sensory feedback impact the asymmetry of local cortical networks and whether increased network symmetry correlates with motor recovery following stroke. Poststroke motor function has been associated with reductions in the integrity of somatosensory pathways (Campfens et al., 2015; Zandvliet, van Wegen, et al., 2020), and recent findings from Zandvliet and colleagues suggest that recovery of somatosensory integrity over time may be necessary for full motor recovery (Zandvliet, Kwakkel, et al., 2020). Additionally, brain controllability studies indicate that application of external stimuli (e.g., via the application of neurofeedback, external sensory stimuli, or electrical stimulation) may be able to shift brain networks into different functional states (Gu et al., 2015; Muldoon et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The measurement van was customized to allow EEG acquisition of the same quality as in our hospital setting. 22 The resting-state EEG measurement analyzed in the current study was part of a larger study protocol. The duration of the full EEG protocol was dependent on patient's ability to perform tasks.…”
Section: Methodsmentioning
confidence: 99%